Physicochemical Characteristics and Water Quality Indices to Assess the Suitability of Groundwater Resources in some Communities of Kogi State, Nigeria - E. O. Akudo; O. Ibrahim; N. M. Muhammad; K. O. Musa; J. B. Ahmed II; G. O. Aigbadon (Journal of Applied Sciences and Environmental Management)
This paper aims to evaluate the physicochemical characteristics and water quality indices (WQI) to assess the suitability of groundwater resources in some communities of Kogi State, Nigeria using appropriate standard procedures. Data obtained show that pH, EC, TDS, and TSS, ranges from 6.18-7.44 (mean – 6.68; std - ± 0.53), 85.26 – 90.23 μS/cm (mean - 88.32 μS/cm; std - ± 2.06 μS/cm), 162-194 mg/l (mean - 174.75 mg/l; std - ± 10.25 mg/l), 24-30 mg/l (27.75 mg/l; std - ± 2.25 mg/l), respectively. The physical parameter results all conformed to WHO standard for ingestible water except pH which presented mild acidity/alkalinity outside the recommended threshold. The chemical parameter results all suggest that the groundwater is not polluted and suitable for consumption. The heavy metals also, showed that the water is safe except aluminum (range – 0.7 – 1.2 mg/l; mean – 0.86; std - ± 0.15), that exceeded the 0.2 mg/l benchmark specified. The computed water quality index (WQI), and heavy metal evaluation index (HEI) revealed that the water is excellent and of low risk for consumption. The groundwater facies and water type indicated that the water is Ca – HCO3 type with bicarbonate dominating the water chemistry. This study further revealed that the groundwater ionic constituent is defined by rock weathering/mineral dissolution and suggest almost zero influence from anthropogenic sources. The water is also found from this research to be fit for consumption and other uses.